Scarred by Your Employer? The Effect of Employers' Strategies on the Career Outcomes of Non-Standard Employment. Issue 3 (August 2022) - Mattijssen, Lucille; Pavlopoulos, Dimitris; Smits, Wendy
In this article, we investigate how the strategies employers have for using non-standard employment – screening, workforce adaptability or cost reduction – affect the career outcomes of workers. To investigate this, we use multichannel sequence analysis to produce a typology of employment and income trajectories of workers with non-standard contracts in the Netherlands. The results show that workers starting employment in firms that use non-standard employment as a screening device are most likely to have careers with high levels of employment security. Strong scarring effects on the career are only found for workers who start employment in firms with cost reduction strategies.